Basal association of a transcription factor favors early gene expression. - Sandrine Pinheiro; Mariona Nadal-Ribelles; Carme Solé; Vincent Vincenzetti; Yves Dusserre; Francesc Posas; Serge Pelet (PLoS Genetics)
Responses to extracellular signals via Mitogen-Activated Protein Kinase (MAPK) pathways control complex transcriptional programs where hundreds of genes are induced at a desired level with a specific timing. Gene expression regulation is largely encoded in the promoter of the gene, which harbors numerous transcription factor binding sites. In the mating MAPK pathway of Saccharomyces cerevisiae, one major transcription factor, Ste12, controls the chronology of gene expression necessary for the fusion of two haploid cells. Because endogenous promoters encode a large diversity of Ste12 binding sites (PRE), we engineered synthetic promoters to decipher the rules that dictate mating gene induction. Conformations of PRE dimers that allow efficient gene expression were identified. The strength of binding of Ste12 to the PRE and the distance of the binding sites to the core promoter modulate the level of induction. The speed of activation is ensured by favoring a basal association of Ste12 by using a strong dimer of PRE located in a nucleosome depleted region.